Classification of International Preferential and Regional Trade Agreements - HOLUBIEVA, Viktoriia О. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).16, 2020)
The article is devoted to comprehensive generalization of features/characteristics of international trade agreements/treaties which introduce/fix certain trade advantages in the tariff and non-tariff spheres. The article identifies fifteen classification features/characteristics of the analyzed international agreements. The features are divided into groups: those simultaneously inherent in all/any mentioned international trade agreements/treaties; those inherent only in international economic integration agreements/treaties; those inherent just in preferential international trade agreements/treaties. Practical relevance: The classification gives an opportunity to suggest some definitions/terms, which take into consideration/involve some separated particulars, namely those of preferential trade agreements, international economic integration agreements, which also include regional trade agreements.